Implementasi Penguatan Profil Pelajar Pancasila Sebagai Wujud Pendidikan Karakter di Sekolah Menengah Atas (SMA) - Depitaria Br Barus; Perida Roma Siahaan; Izmawal Pebriani Nasution; Nova Mawar Hutabarat (Jurnal Bahasa Indonesia Prima (BIP), 2024)
This research is based on the existence of a government policy program in the Project for Strengthening Pancasila Student Profiles in Character Education. This policy cannot be separated from the hope that the nation's children will have character in accordance with Pancasila and the 1945 Constitution. This research uses descriptive qualitative methods. Data collection techniques use interview, observation and documentation methods. Furthermore, data analysis techniques use data reduction, data presentation, conclusion drawing, verification and data validation. The results of this research are 1). Helping schools adopt policies in realizing strengthening the profile of Pancasila as character education through learning, 2). The process of implementing the project to strengthen the profile of Pancasila students is based on the guidelines of the Minister of Education and Culture Decree No. 56 of 2022 Guidelines for Curriculum Implementation, 3). Efforts made to face obstacles include consistent evaluation, creation of modules, annual programs, semester programs adapted to follow-up programs, namely let's act.